1999
DOI: 10.1046/j.1365-201x.1999.00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen cost of dynamic leg exercise on a cycle ergometer: effects of gravity acceleration

Abstract: A model of the metabolic internal power (Eint) during cycling, which includes the gravity acceleration (ag) as a variable, is presented. This model predicts that Eint is minimal in microgravity (0 g; g=9. 81 m s-2), and increases linearly with ag, whence the hypothesis that the oxygen uptake (VO2) during cycling depends on ag. Repeated VO2 measurements during steady-state exercise at 50, 75 and 100 W on the cycle ergometer, performed in space (0 g) and on Earth (1 g) on two subjects, validated the model. VO2 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
2
15
2
Order By: Relevance
“…Incidentally, both experiments were carried out at the same absolute submaximal powers and at the same pedalling frequency. Metabolic data from both studies have been previously published (Girardis et al 1999;Bonjour et al 2010). Cardiovascular data from the same studies are still unpublished.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Incidentally, both experiments were carried out at the same absolute submaximal powers and at the same pedalling frequency. Metabolic data from both studies have been previously published (Girardis et al 1999;Bonjour et al 2010). Cardiovascular data from the same studies are still unpublished.…”
Section: Introductionmentioning
confidence: 92%
“…The volume of the rebreathing bag was empirically established prior to the first experiment; it was increased with the exercise power output and ranged between 2.5 and 3.5 l. During rebreathing, the dry fractions of breathed gases at the mouth were continuously monitored by a photo-acoustic gas analyser (RMS-II, Innovision A/S, Odense, Denmark), stored on a magnetic disk and subsequently analysed by means of the Matlab computation software (Mathworks, USA). The knowledge of bag volume and initial bag SF 6 fraction allowed computation of the overall closed circuit volume, using the dilution principle, as previously described (Girardis et al 1999). _ V O 2 was then computed from the slope of the linear relation between the O 2 volume in the rebreathing bag at end of each expiration and the rebreathing time, as previously described (Girardis et al 1999).…”
Section: Steady-state _mentioning
confidence: 99%
See 1 more Smart Citation
“…According to this equation, _ E I is independent of _ w. It was also demonstrated that _ E I is a power function of the pedalling frequency (f p ) (Francescato et al 1995) and is a linear function of the weight of the legs, that is the product of the mass of the legs (Ml) times the gravity acceleration (a g ) (Girardis et al 1999).…”
Section: The Mechanical Efficiency Of Exercisementioning
confidence: 95%
“…P int was estimated by measuring the mechanical or metabolic energy changes in various studies. The pedaling frequency (Foss and Hallen 2004;Hansen et al 2004;Minetti et al 2001;Prampero et al 1979;Hirakoba 2007, 2008), the mass of the legs (Francescato et al 1995;Kamon et al 1973), and the gravity acceleration (Bonjour et al 2010;Girardis et al 1999) Pint,kiñ Pint,met Fig. 2 The power cascade.…”
Section: Modelmentioning
confidence: 99%